A computer Model of Esophageal Electrical Activity - Podgorski, Maria Elizabeth (My University, 1980)
A chain of 42 bidirectionally coupled relaxation oscillators was used to model electrical activity in the smooth muscle portion of the opossum esophagus. Each oscillator was represented by two first order nonlinear differential equations. The equations were programmed on a Nova 830 minicomputer to develop the model and to test the responses to various stimuli.
The model simulated distally, proximally and bidirectionally propagated contractions (represented by oscillations at 2.5 Hz) when the pulse representing direct muscle stimulation was applied at the beginning, end or in the middle of the chain. Contractions were not present in the absence of a stimulus. The velocity of propagation increased from 3.6 cm/sec among oscillators representing the upper part of smooth muscle to 1.85 cm/sec among distal oscillators representing the lower part of the smooth esophageal muscle.
The model showed "ON" and "OFF" responses upon depolarization or hyperpolarization of the oscillators. The velocity of propagation of "ON" responses was variable and depended upon the amplitude of the stimulus which was applied to all of the oscillators simultaneously. The velocity of propagation of the "OFF" responses was much faster than that of the "ON" responses when the stimulus was applied to all oscillators. The number of spikes in a burst of "OFF" responses was variable and depended upon the amplitude and the duration of the stimulus applied.
In conclusion, the model simulated all of the characteristics observed in the smooth muscle portion of the opossum esophagus. This includes those which were observed on vagal stimulation and balloon distension. The model also elucidates the mechanism of functioning of the myogenic control system and its modulation by the neuronal control system.
Keywords: Electrical and Electronics; Electrical and Electronics